IMPLEMENTASI KEAMANAN E-MAIL DENGAN MENGGUNAKAN PGPTRAY - Alamsyah, Alamsyah (MEKTEK, 2011)
PGP is used to protect electronic mail or e-mail to provide privacy protection by encryption methods.Currently, PGP is not only intended for the security of e-mail but also for the safety of various files and dataon the Personal Computer (PC). Implementation of e-mail security using PGPtray provides convenience andsecurity in the dissemination of information or files and data transformation, and improve security in case ofa hack.. Besides using PGPtray applications where the files or data sent via e-mail in encrypted form so itcan not be read easily by people who do not have reader access files or data.Based on the results obtained that the system design in manufacturing PGPtray applications implementedwith the package installation stage flock, PGPtray installation, configuration PGP icon